Associations of the Geriatric Nutritional Risk Index With Femur Bone Mineral Density and Osteoporosis in American Postmenopausal Women: Data From the National Health and Nutrition Examination Survey - Wang, Jie; Xing, Fei; Sheng, Ning; Xiang, Zhou (Frontiers in Nutrition, 2022)
Background: The geriatric nutritional risk index (GNRI) has be used as a signiﬁcant tool to access nutritional status in the elderly. However, the relationship between the GNRI and femur bone mineral density (BMD) and osteoporosis remain unclear in American postmenopausal women. Objectives: We aim to explore associations of the GNRI with femur BMD and risk of osteoporosis in American postmenopausal women. Methods: We merged the continuous National Health and Nutrition Examination Survey (NHANES) 2005–2006, 2007–2008, 2009–2010, 2013–2014 and 2017–2018 to ensure a large and representative sample, including 3152 participants. The linear relationship between the GNRI and femur BMD was assessed via weighted multivariate linear regression model. The odds ratios (ORs) and 95% confidence intervals (95% CIs) for the association between the GNRI and the risk of osteoporosis was assessed by weighted logistic regression model. Moreover, the nonlinear relationship was also characterized by smooth curve fitting (SCF) and weighted generalized additive model (GAM). Results: After adjusting all covariates, the weighted multivariable linear regression models demonstrated that the GNRI was positively correlated with femur BMD. The weighted logistic regression models demonstrated that each unit of increased GNRI value was associated with 4.13% decreased risk of osteoporosis. When categorizing GNRI based on quartiles, ORs between the risk of osteoporosis and GNRI across quintiles 2, 3 and 4 compared with quintile 1 were 0.5565 (95% CI 0.4791, 0.6463; P <0.000001), 0.5580 (95% CI 0.4600, 0.6769; P<0.000001) and 0.3475 (95% CI 0.2681, 0.4505; P<0.000001). The trends similar to the above were also observed in SCF and GAM. Conclusion: The present study indicated that nutritional status, represented by the GNRI, was positively associated with femur BMD and negatively associated with the risk of osteoporosis in American postmenopausal women. The GNRI may be a good tool to identify American postmenopausal women who need further bone health nutritional support.